Factors Influencing Gen Z's Intention In Adopting Islamic Fintech Payment Digital Services - Syakinah, Fitri (LPPM ISNJ Bengkalis, 2024)
Extensive studies on Islamic financial technology (fintech) have been conducted, while attention to its specific impact on Generation Z still needs to be paid. This research analyses the influence of performance expectancy, effort expectancy, social influence, facilitating conditions, hedonic motivation, price value, and habit on Generation Z's intention to adopt a Sharia-compliant digital fintech payment system. This research uses a survey-based quantitative approach. This research relies on primary data sources through questionnaires. The population of this study was Generation Z from the Garut district, while the sampling technique used random samples using Hair measurements, so 143 samples were obtained. The data analysis technique uses SEM-PLS, assisted by the SmartPLS application. The research results prove that social influence and habit have a positive and significant effect on Generation Z's intention to adopt Islamic fintech digital payment services, while performance expectancy, effort expectancy, facilitating conditions, hedonic motivation, and price value have no effect on Generation Z's intention to adopt payment services Islamic digital fintech. This research can become literature for further research. It can be used as a reference for the Islamic fintech industry to develop products and services that are more attractive to Generation Z.